MARKETING FUNCTION OPTIMISATION TO INCREASE ADDED VALUE AND COMPETITIVENESS OF PALM OIL PRODUCTS: A LITERATURE REVIEW ON THE INTEGRATION OF PURCHASING, SALES, TRANSPORTATION, STORAGE, FINANCING, RISK INSURANCE, QUALITY STANDARDISATION, CLASSIFICATION, AND MARKET INFORMATION - Jeffry H. Sinaulan; Eka budi Yulianti; Sri Sugiarti (INJOSEDU: International Journal of Social and Education, 2026)
This study analyses the optimisation of marketing functions to enhance the added value and competitiveness of Indonesian palm oil products through the holistic integration of eight key functions: purchasing, sales, transportation, storage, financing, risk insurance, quality standardisation, classification, and market information. Using a systematic literature review approach, the study consists of two main discussions: (1) the integration of operational functions that reduce transaction costs by 20-30% through the synchronisation of digital supply chains; and (2) the integration of strategic functions that support national downstreaming with a multiplier effect of Rp 3.2 trillion per Rp 1 trillion investment through sharia KUR financing, parametric insurance, and ISPO certification. The findings confirm that current marketing fragmentation causes disparities in farmer margins of £47-305/kg of fresh fruit bunches and only 65% utilisation of palm oil mills, which can be addressed through an integrated ERP-IoT-blockchain platform. Strategically, this optimisation strengthens Indonesia's position as a 55-60% global palm oil producer, supports B40 biodiesel, and meets EUDR regulations for sustainable competitiveness until 2035